1994
DOI: 10.1152/ajprenal.1994.266.5.f797
|View full text |Cite
|
Sign up to set email alerts
|

Urate transport in brush-border membrane of human kidney

Abstract: Mechanisms of urate transport were investigated in human renal brush-border membrane vesicles. The imposition of an outwardly directed Cl- gradient, in voltage-clamp and pH-clamp conditions, stimulated [14C]urate uptake. Organic anions, including pyrazinoate (PZA), probenecid, lactate, ketone bodies, succinate, and alpha-ketoglutarate in their monovalent forms, cis-inhibited [14C]urate uptake. The affinity order was PZA > urate > probenecid > other anions. Vesicle preloading with these anions trans-stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 0 publications
5
56
0
3
Order By: Relevance
“…Based on our current findings (Figures 2-5) we conclude galectin 9 need not invariably be a cytoplasmic or secreted protein, but rather that it may reside as an integral protein in the lipid bilayer of plasma membranes where it may serve an important transport function, at least in renal epithelial cells. Additionally, insofar as recombinant hUAT functions as a selective urate channel (Figure 2), we suggest that hUAT is likely to be the molecular representation of the electrogenic transporter that functions to secrete urate into the proximal tubule of the human kidney (13). Since excreted urate is generally thought to derive primarily from secreted urate (45,46), perturbations in this transporter could modify the ability of the kidney to eliminate urate from the body.…”
Section: Discussionmentioning
confidence: 94%
“…Based on our current findings (Figures 2-5) we conclude galectin 9 need not invariably be a cytoplasmic or secreted protein, but rather that it may reside as an integral protein in the lipid bilayer of plasma membranes where it may serve an important transport function, at least in renal epithelial cells. Additionally, insofar as recombinant hUAT functions as a selective urate channel (Figure 2), we suggest that hUAT is likely to be the molecular representation of the electrogenic transporter that functions to secrete urate into the proximal tubule of the human kidney (13). Since excreted urate is generally thought to derive primarily from secreted urate (45,46), perturbations in this transporter could modify the ability of the kidney to eliminate urate from the body.…”
Section: Discussionmentioning
confidence: 94%
“…Urate uptake into human renal BBMV was noted to be strongly stimulated by an outwardly directed Cl Ϫ gradient (19).…”
Section: Discussionmentioning
confidence: 98%
“…In earlier vesicle studies, Roch-Ramel et al (19) postulated the existence of two different urate exchangers, one with high affinity for urate and aromatic molecules, such as nicotinate, pyrazinoate, and orotate, which now is represented by hURAT1, and a second, low-affinity urate transporter that exchanges urate against OA or chloride (27). Moreover, they demonstrated that an OH Ϫ ion gradient provokes urate uptake into human brush border membrane vesicles (BBMV), a transport mode, which is not covered by hURAT1 (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, no chicken orthologs of these two transporters have yet been identified; they are Cl -sensitive and they do not have the BBMV urate transport properties, i.e. they are not electrogenic antiporters (Roch-Ramel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Among the vertebrates, the modalities of urate transport across the apical membranes of the proximal tubule epithelium include electroneutral anion exchange (Enomoto et al, 2002;Guggino et al, 1983), electrogenic urate transport (Grassl, 2002a;Roch-Ramel et al, 1994) and primary active transport (Van Aubel et al, 2005). The last two processes have been associated with urate secretion, and NPT1 (sodium-phosphate transporter I; Uchino et al, 2000), Oat v 1 (voltage-dependent organic anion transporter 1; Jutabha et al, 2003) and MRP4 (multidrug resistance peptide 4; Van Aubel et al, 2005) have been proposed as candidate transporters.…”
Section: Introductionmentioning
confidence: 99%